اسس التخطيط الاجتماعي دراسة نظرية تطبيقية في التخطيط الاجتماعي - حسين, حسن عجيل (Sulaimani Journal for Humanities, 2000)
Throughout history, human civilization has carried clarified facts, itch were all about humans attempts to in spectate the things that make them to live in peace .Many of these attempts witch were reflected by different civilizations made by man from the early time till this moment, have been kept in the file of history .Man's attempts in his study of history is nothing more than evidence of his astonishment about what it him at the present and what threatens him in the future .In different wars and events resulting damages . To overcome such a kind of problems, It becomes necessary to study and pay attention to different aspects of life in society, for it's development toward be stand to make social establishments to different services for the members of the society kin this base, the shortages of society and the nature of developing different options become on important matter .That shouldn't be ignored either in planning or in social arrangement or social changes planned before hand! For social factors represent a vital role in creating many social and complex problemsi On this base there must be a controlling program and establishing projects to undertake social life in it's best form. This is considered as the major aim in new society and developing countries, witch attempt to develop their society socially and economically, in order to go on within the development of civilization. This research consists of four parts: part one deals with limiting the concept and method of the research whereas part two explains planning according to the point of view sociology, emphasizing the construction, function and problems. part three deals with planning spaces through individual, group and social services. part four which the last one deals with planning administrations and social planning according to planning administrations and social planners experiences and the features of social planner and finally we have list of contents and bibliography.